Hygrothermal aging and water absorption behavior of radial tire composites. Issue 13 (9th November 2021) - Jiang, Ning; Li, Mengdi; Li, Di; Li, Yuankun; Zhang, Ru; Song, Hui; Liu, Xingfeng; Ge, Wenqing; Li, Ning; Chen, Chaozhong
Abstract: Radial tires (RT) are widely used in the automobile. However, the moisture absorption characteristics of the tire in the hygrothermal environment accelerate tire aging and affect the service life. This work focused on the water absorption behavior and durability of RT composites in the hygrothermal environment. The effects of aging in water at 30, 60, and 90°C on water absorption, chemical degradation, and internal structure of RT composites were investigated. The results showed that the water diffusion of RT composites followed the Fickian's law of diffusion in the initial stage. The kinetic parameters of water absorption were also determined at this stage and were closely related to the change of temperature. Then, moisture led to the poor interface and the degradation of RT composites. Natural rubber (NR) matrix swelled due to the invasion of water, which developed stresses that could cause microcracks of the matrix in the second stage. Moreover, moisture promoted hydrolysis of the NR matrix and agents in the third stage. The water molecules existed in unbound water and bound water, which made the water diffusion followed the Langmuir adsorption model. Abstract : The rubber composite samples were prepared from natural rubber and additives. After hygrothermal experiments, it was found that rubber composites have different water absorption characteristics at three temperatures (30, 60 and 90 ℃), and the water diffusion behavior conforms to Langmuir adsorption model rather than the classical Fickian law.